FORMATION OF SOFT SKILLS IN FUTURE SPANISH AND ITALIAN TRANSLATORS IN THE CONTEXT OF CROSS-CULTURAL COMMUNICATION - Taras Pysmennyi; Marina Pavlovich; Yuliia Tiapina (Alfred Nobel University Publisher, 2020)
Given the growing activity of the integration processes and globalization of cultures, peoples, states and society as a whole, there is an increasing need to modernize and improve the practical and professional skills and abilities of all professions without exception that are somehow related to crosscultural, international or, as they are called, international communications and interactions. And translators of foreign languages in the context of the development of cross-cultural communications are in the first place, because they are the key figures in the negotiation process at various levels, from meetings in an informal setting to important business negotiations or diplomatic events. The solution of important local, interregional, interstate or even international issues often depends on the competence and perfection of the translator's knowledge. The problem of correct interpretation and translation in the context of crosscultural communication is especially relevant for translators of cognate languages. Spanish and Italian were taken as an example since they originate from the Latin language and are similar in many aspects. Therefore, we can say that Spanish-Italian or Italian-Spanish translation is difficult to implement in the context of intercultural communication. The authors of the article have analyzed the list of flexible skills of Spanish and Italian translators in the context of cross-cultural communication and have developed practical exercises and recommendations for their application. In the future, the authors plan to consider each of the flexible skills features in details, to work out a set of methodological and practical exercises for their development